Inhibition of Xanthomonas fragariae, Causative Agent of Angular Leaf Spot of Strawberry, through Iron Deprivation - Henry, Peter M.; Gebben, Samantha J.; Tech, Jan J.; Yip, Jennifer L.; Leveau, Johan H. J. (Frontiers in Microbiology, 2016)
In commercial production settings, few options exist to prevent or treat angular leaf spot of strawberry, a disease of economic importance and caused by the bacterial pathogen Xanthomonas fragariae (Xfr). In the process of isolating and identifying Xfr bacteria from symptomatic plants, we observed growth inhibition of Xfr by bacterial isolates from the same leaf macerates. Identified as species of Pseudomonas and Rhizobium, these isolates were confirmed to suppress growth of Xfr in agar overlay plates and in microtiter plate cultures, as did our reference strain Pseudomonas putida KT2440. Screening of a transposon mutant library of KT2440 revealed that disruption of the biosynthetic pathway for the siderophore pyoverdine resulted in complete loss of Xfr antagonism, suggesting iron competition as a mode of action. Antagonism could be replicated on plate and in culture by addition of purified pyoverdine or by addition of the chelating agents tannic acid and dipyridyl, while supplementing the medium with iron negated the inhibitory effects of pyoverdine, tannic acid and dipyridyl. When co-inoculated with tannic acid onto strawberry plants, Xfr’s ability to cause foliar symptoms was greatly reduced, suggesting a possible opportunity for iron-based management of angular leaf spot. We discuss our findings in the context of ‘nutritional immunity’, the idea that plant hosts restrict pathogens access to iron, either directly, or indirectly through their associated microbiota.